Interleukin‐6 and acute coronary syndrome - Ikeda, Uichi (Clin Cardiol, 2009)
The designation of atherosclerosis as a chronic inflammatory process represents an exciting and logical paradigm shift for cardiologists. Plasma concentrations of interleukin‐6 (IL‐6) and its hepatic by‐product C‐reactive protein (CRP) appear to reflect the intensity of occult plaque inflammation and by inference may determine vulnerability to rupture. Indeed, circulating IL‐6 levels are elevated in patients with acute myocardial infarction (AMI), and also in patients with unstable, but not with stable angina. Coronary sinus IL‐6 concentrations are also increased after percutaneous coronary intervention (PCI), and late restenosis correlates with an increase in IL‐6 concentration after the procedure, indicating that IL‐6 expression may be not only related to instability of atheromatous plaques, but also to the formation of restenotic lesions after PCI. These observations suggest the advantage of screening for circulating IL‐6 concentration and the use of anti‐inflammatory treatment for those thought be at high risk to reduce the risk of future AMI.